Membangun Persepsi Relasi Keluarga Islami Melalui Pelatihan Pra-Nikah di Mahad Sunan Ampel Al-Aly - Chotimah, Dien Nur; Sutaman, Sutaman (Jurnal Pemberdayaan Masyarakat, 2023)
This community service aims to build a perception of Islamic family relations for the administrators of Mahad Sunan Ampel Al-Aly Malang.  This is very important to do because today's millennial generation really needs coaching related to building husband and wife relationships in the family.  Coaching program to the administrators of Mahad Sunan Ampel Al-Aly is a very strategic step, because they will pass on this perception to the students whoare  under their responsibility. This community service is carried out with two cycles of Participatory Action Research (PAR) methods that manifests in two main activities, namely focus goup discussions together with the management of Mahad Sunan Ampel Al-Aly and implementing pre-marital training.  From the pre-marital training conducted, 64.1% increased the perception of Islamic family relations in the administrators of Mahad Sunan Ampel Al-Aly Malang. In addition, a joint commitment was also produced as a follow-up to activities in the form of delivering training materials to  the assisted students of each participant.